Recognizing Ministry of Entrepreneur Development and Cooperation (MEDEC) in the furtherance interest of entrepreneurs and cooperatives - Irma Wani Othman; Haslinda Hassan; Siti Nor Bayaah Ahmad; Salmah Topimin; Merlyn Rita Anak Buncha (Academic Inspired Network, 2022)
This article focuses on a balanced, integrated, and blended effort in facing the continuation of the endemic era of COVID-19 in the economic sector engaging entrepreneurs and cooperatives. The purpose of the discussion is to identify the dispute over the role, government efforts, and MEDAC's strategy in assisting entrepreneurs and cooperatives to maintain a stable momentum in their businesses. This paper attempts to address the following issues: (i) Visibility of MEDAC's role and responsibilities (ii) Immediate priority for the target group affected by the Covid-19 pandemic (iii) Financial aid channelled to reach the target group and the effect of cash flow on aid recipients, and (iv) Introduction and implementation of the Cooperative Intervention Plan. This paper uses secondary sources, such as study results published in journals, scholarly literature, internet news sources, and public forums, to employ a qualitative methodology. According to the findings of the study, the government's approach provides assistance to entrepreneurs particularly the B40 group, the disabled, the urban poor, rural communities, inland communities, and indigenous people who have been impacted by COVID-19, where it has a positive impact that leads to the implementation of a comprehensive transformation for sustainable economic growth. The goal of the study is to determine the drastic steps that must be made in the era of the endemic Covid-19 in order to create a holistic and hospitable entrepreneurial environment to support the nation's inclusive, sustainable, and knowledge-driven entrepreneurship development plan.